Evolution of the permanence and education of rural youth in Brazil and Colombia: A historical-comparative analysis - Triana, Jorge; Vinicius Brisola, Marlon; Valle Lima, Suzana Maria (Cooperativismo & Desarrollo, 2020)
In this article a comparative analysis is carried out in the last decade between Colombia and Brazil, evaluating the situations that influence the rural exodus of the youth, based on bibliographical surveys, data and arguments that prove this hypothesis. The text ends by presenting the results and analyzes that provide information for the improvement of the research in the field of rural youth.
Keywords: solidary associativity; education; migration; rural youth; Brazil; Colombia